Synthesis and characterization of SSS/MA/NVCL copolymer as high temperature oil well cement retarder. Issue 9 (1st July 2022) - Zhang, Chi; Jin, Jianzhou; Xu, Weining; Yang, Junlan; Li, Ming
Abstract: Oil well cement additives applied in high-temperature environments play an increasingly important role in well cementing work. In this study, a ternary copolymer LNS-1 consisting of sodium styrene sulfonate (SSS), maleic acid (MA), and N-vinylcaprolactam (NVCL) was designed and synthesized using potassium persulfate as an initiator via free radical aqueous solution copolymerization, which was then used as a retarder additive for oil well cement under high-temperature conditions. The structure and performance of copolymer LNS-1 was assessed via gel permeation chromatography, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance hydrogen spectrum, Thermogravimetric analysis, and scanning electron microscopy analysis. To study the effect of the retarder on cement slurry properties, the performance of the slurry with LNS-1 was tested. The experimental results demonstrate that LNS-1 was successfully synthesized with excellent retarding ability, thermal resistance, and outstanding suspension; thus, the copolymer can serve as an excellent retarder for oil well cement. Through exploration, it is found that the mechanism of the retarder mainly includes adsorption – membrane layer mechanism and chelation – covering mechanism. NVCL exhibits good complexation, adsorption, hydrolysis stability, and thermal stability. It contains three lone pairs of electrons, which allow the NVCL to chelate Ca 2+ that in the liquid phase of the cement. The number of calcium ions is therefore reduced in the cement liquid phase, and cement hydration is inhibited to a certain extent, contributing to a longer hydration process. Graphical Abstract: UF0001